VISUAL OUTCOMES AND COMPLICATIONS OF IRIS-CLAW INTRAOCULAR LENS IMPLANTATION IN APHAKIC EYES WITH INADEQUATE CAPSULAR SUPPORT - Faiz Nurboston Fauzi; Dini Dharmawidiarini; Farida Moenir; Sahata PH Napitupulu (Majalah Oftalmologi Indonesia, 2023)
Introduction: Aphakia with inadequate capsular support remains a challenge for ophthalmologist. Although there is no consensus on the best method for this case, many studies have been reported using iris claw intraocular lens for secondary implantation. Objective: To evaluate the various indications, visual outcomes, and complications of iris claw intraocular lens in aphakic eyes. Methods : This retrospective case study was conducted in Undaan Eye Hospital, Surabaya, collecting data from medical records with a total of 188 eyes of 186 patients between May 2017 and April 2020, that were rehabilitated with prepupillary and retropupillary fixation of an iris claw lens. Patients were followed-up to 9 months for visual acuity and complications. Results: The most common cause of aphakia was subluxation of lens (spontaneous, trauma or congenital) in 90 of the 188 eyes (47.3%). The mean follow-up was 3 months (range :1-9 month). Most patient had the best preoperative BCVA (0-0.50 logMAR) 63%, ranging 0-2.47 logMAR with a mean of 0.72 logMAR. At final follow up, of the total patients, 72.9 % had the BCVA of 0-0.5 logMAR, with a mean of 0.37 logMAR. Complication included secondary glaucoma 2.12%, uveitis 1.06 %, iridodyalisis 1.06 %, and bullous keratopathy 1.06%. Conclusion: iris claw IOL implantation is a safe and effective method of rehabilitating aphakic eye with inadequate capsular support.